Patellofemoral osteoarthritis is prevalent and associated with worse symptoms and function after hamstring tendon autograft ACL reconstruction. Issue 6 (27th November 2013) - Culvenor, Adam G; Lai, Courtney C H; Gabbe, Belinda J; Makdissi, Michael; Collins, Natalie J; Vicenzino, Bill; Morris, Hayden G; Crossley, Kay M
Abstract : Objectives: To evaluate the compartmental distribution of knee osteoarthritis (OA) after anterior cruciate ligament reconstruction (ACLR), to determine if patellofemoral or tibiofemoral OA is more strongly associated with knee symptoms and function, and to evaluate the contribution of associated injuries and surgical delay to the development of OA. Methods: This cross-sectional study recruited 70 participants who underwent hamstring tendon (HT) ACLR 5–10 years previously. Radiographic OA was assessed according to the Osteoarthritis Research Society International (OARSI) criteria. Knee symptoms were assessed with the Knee Injury and Osteoarthritis Outcome Score (KOOS) and Anterior Knee Pain Scale (AKPS), while function was assessed with three lower limb tasks (hop-for-distance, one-leg rise and side-hop). Multivariate and binary logistic regression analyses were performed to assess the relationship between OA and symptomatic/functional outcomes and associated injuries/surgical delay, respectively. Results: Radiographic OA was observed in the patellofemoral (47%) and tibiofemoral joints (31%). Pain, symptoms and quality of life on the KOOS and the AKPS were associated with severity of patellofemoral OA (standardised regression coefficient (β)=−0.3 to −0.5, p=0.001–0.042), whereas only the KOOS-pain subscale was associated with tibiofemoral OA (β=−0.3, p=0.037). For each functional task, greater patellofemoral OA severity was associated with worse performance, independent of tibiofemoral OA severity (β=−0.3 to −0.4, p=0.001–0.026). Medial meniscal and patellofemoral chondral lesions at surgery were associated with tibiofemoral and patellofemoral OA development at follow-up, respectively, while a longer surgery delay was associated with patellofemoral OA. Conclusions: Patellofemoral OA is common following HT ACLR and is associated with worse knee-related symptoms, including anterior knee pain, and decreased functional performance.